Associated factors with the prescription of potentially inappropriate medication for older adult in a public hospital - Priscilla M. SOUZA; Rafaela L. SANTOS; Monique G. CERQUEIRA; Gildomar L. VALASQUES-JUNIOR; Tuany S. SOUZA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To evaluate the factors associated with the prescription of potentially inappropriate medications for the older adult (PIM) in a public hospital. Methods: A prospective cross-sectional study was carried out, whose data were collected from the medical records of older adult patients, admitted to the medical clinic of a public hospital, by a trained researcher, not a member of the staff. The collection took place between November 2018 and January 2019. The medical records of patients aged over 60 years, who were using at least one allopathic in-hospital medication, with a minimum of 48 hours of hospitalization, were included. Illegible prescriptions, or those containing only herbal medicines and / or vitamin supplements, were excluded. The PIMs were classified according to the Beers Criteria, 2019 update. Descriptive analysis of the data was performed using frequencies, means and standard deviation and bivariate analysis using the Chi-square and Fisher's Exact tests, with a level of significance. p <0.05, using the software and SPSS® v.21.0. Results: 42 medical records of the older adult were analyzed, where a 100% prevalence of use of PIM and polypharmacy was identified. The number of PIMs per patient was significantly associated with females (p = 0.020), with a higher prevalence of older adult women who used between 1 and 4 PIMs (64.1%); diagnosis (p = 0.006), with a higher prevalence of older adult people with circulatory tract diseases (54.5% using 1-4 PIM), endocrine, nutritional and metabolic diseases (85.7% using 1-4 PIM) ) and diseases of the circulatory system (83.5% in use ≥5 PIM); polypharmacy (p = 0.002) with  higher prevalence of older adult people who used ≥10 medications (52%, in use ≥ 5 PIM). The main therapeutic classes of PIM were of the alimentary tract and metabolism (46%) and nervous system (22%). Conclusion: It is concluded that the prescription of PIM was very high, where all the older adult in this study were exposed, being significantly associated with the female gender, polypharmacy, and diagnoses related to chronic comorbidities. It is necessary to raise the awareness of the team to adopt safer strategies and practices in the use of these drugs in order to minimize the exposure of the older adult to possible risks.